College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter P, Prerequisites - Section P.6 - Factoring - P.6 Exercises: 28

Answer

$(a-6b)(a+6b)$

Work Step by Step

The given expression can be written as: $=a^2-6^2b^2 \\=a^2-(6b)^2$ RECALL: $A^2-B^2=(A-B)(A+B)$ Factor the difference of two squares using the formula above with $A=a$ and $B=6b$ to obtain: $=(a-6b)(a+6b)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.